Ecclesiastical Prisons and Royal Authority in the Reign of Henry VII - McGlynn, Margaret (The journal of ecclesiastical history, 2019)
After his appointment as chief justice of King's Bench in 1495, John Fyneux pressured the ecclesiastical hierarchy through indictments for escapes which explored which officials had responsibility for the prisons and how they were managed, and thereby successfully asserted the royal right of oversight. By the end of Henry VII's reign his bishops, faced with ruinous fines like other lords, had largely accepted their role as gaolers under royal authority, and thus contributed to the bureaucratisation of the hierarchy which Henry VIII would exploit to such good effect.